Análise de indicadores financeiros para precificação de oferta pública inicial - Wang, Carolina [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
Companies with a different concept, Startups, are growing more and more in Brazil and with it the constant search for investors as well. There are several ways to raise money for the company, but the most complex and desired is the launch of an IPO, ie listing stocks on the stock exchange. The process for this event is long, requires several reports and audits. One of the major difficulties is understanding what the impact of the monthly financial indicators of years impacted on the final share price. For this, this work was calculated in the Banco Inter Valuation, a stock exchange listed on the São Paulo Stock Exchange, showing the practice of the importance of analyzing and retaining a company's historical data. It was adopted as the basis the method of calculation of the Ministério da Fazenda, using great security of the tool.

Empresas com um conceito diferente, as Startups, estão crescendo cada vez mais no Brasil e com isso a constante busca por investidores também. Existem diversas formas para se captar dinheiro para a companhia, porém a mais complexa e desejada é o lançamento de um IPO, ou seja, listar ações na Bolsa de Valores. O processo para esse acontecimento é longo, demanda diversos relatórios e auditorias. Uma das grandes dificuldades é entender qual o impacto de indicadores financeiros mensais de anos impactam no preço final da ação. Para isso neste trabalho foi calculado o Valuation do Banco Inter, a fintech listada na Bolsa de Valores de São Paulo, mostrando na prática a importância da análise e retenção de dados históricos de uma empresa. Foi tomado como base o método de cálculo do Ministério da Fazendo, garantindo grande segurança da ferramenta.
Analysis of financial indicators for initial public offering opening price
Keywords: Valuation; Capital Opeing; IPO; Abertura de Capital; Oferta pública inicial de títulos (Finanças); Indicadores econômicos; Administração financeira